2020
DOI: 10.1002/dys.1656
|View full text |Cite
|
Sign up to set email alerts
|

School‐entry language outcomes in late talkers with and without a family risk of dyslexia

Abstract: Children with familial risk (FR) of dyslexia and children with early language delay are known to be at risk for later language and literacy difficulties. However, research addressing long‐term outcomes in children with both risk factors is scarce. This study tracked FR and No‐FR children identified as late talkers at 2 years of age and reports development from 4;6 through 6 years. We examined the possible effects of FR‐status and late talking (LT) status, respectively, on language skills at school entry, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(128 reference statements)
2
2
0
Order By: Relevance
“…Proportions of children with persistent versus transient language delay in the current study were similar to those of previous studies (Caglar-Ryeng et al, 2020;Ellis Weismer, 2007;Law et al, 2000;Rescorla & Dale, 2013). In addition, in line with previous studies, there were differences in early receptive skills between children with transient language delay and those with persistent language delay (Bishop & Edmundson, 1987;Ellis Weismer, 2007;Ghassabian et al, 2014;Rescorla & Dale, 2013).…”
Section: Stability Of Language Skills Into the Elementary School Yearssupporting
confidence: 90%
See 2 more Smart Citations
“…Proportions of children with persistent versus transient language delay in the current study were similar to those of previous studies (Caglar-Ryeng et al, 2020;Ellis Weismer, 2007;Law et al, 2000;Rescorla & Dale, 2013). In addition, in line with previous studies, there were differences in early receptive skills between children with transient language delay and those with persistent language delay (Bishop & Edmundson, 1987;Ellis Weismer, 2007;Ghassabian et al, 2014;Rescorla & Dale, 2013).…”
Section: Stability Of Language Skills Into the Elementary School Yearssupporting
confidence: 90%
“…Similar to Bishop and Adams (1990), we found that children with persistent language delay showed continuing difficulties in vocabulary and morphosyntax at the beginning of school age. Though methods used in the current study do not allow to identify/ diagnose DLD, this language profile is consistent with DLD (Caglar-Ryeng et al, 2020;Ellis Weismer, 2007;Rescorla, 2013).…”
Section: Stability Of Language Skills Into the Elementary School Yearssupporting
confidence: 60%
See 1 more Smart Citation
“…Individual differences in language skills are already present in young children from the first years of life. These differences are relatively stable when children pass the age of 1 year, meaning that low language levels are persistent, not only for children with DLD but also for the so-called “late talkers” (Bornstein et al, 2018; Caglar-Ryeng et al, 2021). This does not mean that language is not malleable: especially early in life language skills can be improved by intervention.…”
Section: Introductionmentioning
confidence: 99%